Modern defining characteristics of innovative development of the ukrainian economy: theoretical and practical aspects - Olena Iastremska; Lyudmyla Malyarets; Olesia Iastremska; Igor Barannik (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the article is theoretical substantiation, methodological support, and practical proposals for studying the innovative development of the economy in modern conditions. The aim of the study is to generalize and improve the theoretical foundations of innovative development, identify the main influencing factors and defining characteristics of its course and develop proposals to ensure innovative development of Ukraine's economy in the current conditions. The following tasks have been defined: to find out the attitude of specialists to the possibility and necessity of supporting innovative development in today's difficult military conditions; to summarize the theoretical basis of innovative development and improve its definition and group existing concepts; to substantiate the most influential factors that determine the intensification and/or containment of innovative development of the Ukrainian economy; to identify its defining characteristics, which are used to generate measures to ensure innovative development of the economy in wartime conditions. To solve the tasks, the following methods were used: theoretical generalization, analysis, synthesis, induction, deduction, structural and logical analysis, systemic and situational approaches, economic and statistical analysis, correlation analysis, multivariate regression analysis, graphical method. The following results have been obtained: the definition of the concept of "innovative development" has been improved; the concepts of innovative development have been analyzed; the main factors influencing the course of innovative development in Ukraine have been identified; multivariate regression models have been built according to the influential factors of innovative development and the most important of them have been substantiated; the current defining features of innovative development of the Ukrainian economy have been identified by significant factors and their specification has been carried out in accordance with the measures to ensure it in the conditions of military operations. Conclusions. It is proved that the improved concept of "innovative development" is that it characterizes the resolution of obvious and hidden contradictions on the basis of qualitative changes in the economic system through the accumulation of quantitative transformations in its components and/or factors of innovation processes, intellectual property, the latest technologies and products. In accordance with the above generalized concepts of innovation development, the author investigates the factors influencing this phenomenon based on the dynamics of the components of the global innovation index and statistical indicators of Ukraine's economy for the period 2015–2022. The most influential factors according to the outlined indicators are identified and multivariate regression models are built, which reveal the following modern leading features of innovation development: formation and maintenance of solvent demand of end users (customers) of innovations for the acquisition of intellectual property. With this in mind, the author proposes measures to ensure and intensify innovative development in the context of military operations in Ukraine.